The use of pioglitazone and the risk of bladder cancer in people with type 2 diabetes: nested case-control study. (31st May 2012) - Azoulay, Laurent; Yin, Hui; Filion, Kristian B; Assayag, Jonathan; Majdan, Agnieszka; Pollak, Michael N; Suissa, Samy
Abstract : Objective To determine if the use of pioglitazone is associated with an increased risk of incident bladder cancer in people with type 2 diabetes. Design Retrospective cohort study using a nested case-control analysis. Setting Over 600 general practices in the United Kingdom contributing to the general practice research database. Participants The cohort consisted of people with type 2 diabetes who were newly treated with oral hypoglycaemic agents between 1 January 1988 and 31 December 2009. All incident cases of bladder cancer occurring during follow-up were identified and matched to up to 20 controls on year of birth, year of cohort entry, sex, and duration of follow-up. Exposure was defined as ever use of pioglitazone, along with measures of duration and cumulative dosage. Main outcome measure Risk of incident bladder cancer associated with use of pioglitazone. Results The cohort included 115 727 new users of oral hypoglycaemic agents, with 470 patients diagnosed as having bladder cancer during follow-up (rate 89.4 per 100 000 person years). The 376 cases of bladder cancer that were diagnosed beyond one year of follow-up were matched to 6699 controls. Overall, ever use of pioglitazone was associated with an increased rate of bladder cancer (rate ratio 1.83, 95% confidence interval 1.10 to 3.05). The rate increased as a function of duration of use, with the highest rate observed in patients exposed for more than 24 months (1.99, 1.14 to 3.45) and in those with a cumulative dosage greater than 28 000 mg (2.54, 1.05 to 6.14). Conclusion The use of pioglitazone is associated with an increased risk of incident bladder cancer among people with type 2 diabetes.